Building Professional Relationships with Students: The Key to Focusing on Needs of the Market Trends - Andreea-Maria Sărmașiu (Educaţia 21)
In the context of an increasingly dynamic and competitive job market, the cultivation of professional relationships between academia (professors and students) and different professional fields has emerged as an extremely important factor in addressing contemporary industry demands. Our study examines the critical role of fostering professional interactions in educational settings to align with the current market requirements, namely with some specialized fields (multilingual professional communication, general and specialized translation, and interpreting). Our paper aims to emphasize the role of professors in extending their roles beyond traditional pedagogy to include mentorship, guidance that integrates industry insights, tailored career advice, and practical applications. This research utilizes a “mock” service-learning project to demonstrate the positive outcomes of proactive professor-student engagements on career readiness and adaptability to market shifts. The most important findings of our project are reflected on the pedagogical approach that bridged the gap between academic theory and practical application by enhancing learning (academic concepts were applied to real-world scenarios), impacting the business community (significant and positive impact on addressing immediate needs and long-term collaborations between higher education institutions and business communities), contributing to personal growth, and preparing for future careers.